Formulation and Antibacterial Activity Test of Dragon Tail Leaf Extract Cream (Rhaphidophorapinnata (L.f) Schott) Against Staphylococcus aureus ATCC (25923) - Mutia Della Citra; Bangkit Riska Permata; Kharisma Jayak Pratama (CV. AFDIFAL MAJU BERKAH, 2025)
This study aims to formulate a cream containing Rhaphidophora pinnata (L.f) Schott leaf extract and evaluate its antibacterial activity against Staphylococcus aureus ATCC 25923. The background of this research is rooted in the potential of Indonesian medicinal plants and the increasing cases of antibiotic resistance, which drives the development of natural antibacterial agents. A quantitative experimental laboratory method was employed. The study population was the Rhaphidophora pinnata plant from Sragen, with a sample of 8 kg of fresh leaves. Antibacterial activity was tested using the disc diffusion method, and data were analyzed descriptively and inferentially using One-Way ANOVA with SPSS. The results showed that cream formulations at 10%, 30%, and 40% concentrations had physical qualities that met standards, including a safe pH (6.0–6.8) and stable viscosity. The antibacterial test demonstrated the highest activity at the 40% concentration, producing the largest inhibition zone against S. aureus. However, its efficacy was still lower than that of the positive control (gentamicin cream). In conclusion, R. pinnata leaf extract has the potential to be developed as a natural antibacterial cream, and further research is needed for stability and clinical testing.